A‐Ring‐Modified 2‐Hydroxyethylidene Previtamin D3 Analogues: Synthesis and Biological Evaluation. Issue 3 (3rd January 2017) - Hernández‐Martín, Alba; Fernández, Susana; Verstuyf, Annemieke; Verlinden, Lieve; Ferrero, Miguel
Abstract : To investigate the biological profile of the previtamin form of vitamin D, we synthesized new analogues of 19‐ nor ‐1α, 25‐dihydroxyprevitamin D3 bearing a 2‐hydroxyethylidene moiety at the A‐ring. The target compounds were prepared by convergent synthesis using a Sonogashira coupling between an A‐ring enyne synthon and a CD‐ring/side‐chain vinyl triflate. We have demonstrated the versatility of shikimic acid as a starting material for the synthesis of the A‐ring precursors. The binding affinity to vitamin D receptor (VDR) and human vitamin D binding protein (hDBP), and the MCF‐7 cell antiproliferative activity were evaluated. Abstract : The synthesis of previtamin D3 analogues with a 2‐hydroxyethylidene group in the A‐ring is described. The strategy involves coupling of a dienyne precursor of the A‐ring derived from shikimic acid with an enol triflate of the CD‐ring/side‐chain fragment. The binding affinity to vitamin D receptor (VDR) and human vitamin D binding protein (hDBP), and the MCF‐7 cell antiproliferative activity is discussed.